YOSIKA PROFESIONALISM AS PUJANGGANONG FIGURE IN REYOG OBYOK PERFORMANCE IN PONOROGO REGENCY - Ramadhan, Alfian Arif; Rahayu, Eko Wahyuni Rahayu Wahyuni (Sembadra, Journal of Arts and Education Studies, 2021)
Yosika is the name of a young man in Ponorogo who is involved in the art of Reyog Ponorogo, whose main role is as a Pujangganong dancer. His proficiency in playing the character Pujangganong led him to become a professional dancer and well-known artist. This article aims to reveal Yosika's professionalism in her role as a Pujangganong dancer. This research uses descriptive qualitative methods with data collection techniques through observation, interviews, and documentation study. The results showed that Yosika's profession as a Pujangganong dancer in the Reyog Ponorogo show had been built since she was a child. With the support of the whole family and armed with perseverance, Yosika was finally able to reach the pinnacle of her career as a professional dancer in the Reyog Ponorogo show, especially for the character Pujangganong. Profesionalisme Yosika professionalism can be seen through his performance in taking a role as Pujangganong in Reyog Ponorogo, particularly in Reyog Obyok. Through the style of Pujangganong appearance performed by Yosika, Reyog Ponorogo art is adapt to the present demand and make a lot of people, especially young generation admire this art performance. Through Yosika professionalism as Pujangganong character, Reyog Ponorogo has a hope to be continually exist in the future time, which definitely help to preserve the extinction of Reyog Ponorogo performing arts. Keywords: professionalism, Yosika, Pujangganong, Reyog Obyok